PELATIHAN DAN PENDAMPINGAN PENYUSUNAN PERENCANAAN USAHA PADA USAHA TERPADU KALIBOTO GREEN INSTITUTE (KGI) KECAMATAN MOJOGEDANG, KABUPATEN KARANGANYAR - Rohwiyati; Kim Budiwinarto; Juni Trisnowati; Praptiestrini; sulistyo; Yanti Sri Danarwati; Giarti Slamet; Dewi Pujiani; handayani (SURAKARTA ABDIMAS JOURNAL, 2023)
Abstract Kaliboto Green Institute (KGI) is a business activity: economy, environment and education have the potential as one of the nodes and multiplyer effects for economic activities around Mojogedang District. In this regard, the PKM Team of the Faculty of Economics, University of Surakarta was present at community service activities, by making training and assistance in preparing business plans, especially for the category of novice entrepreneurs. Prior to the training, a survey was conducted to. Training on business plan preparation is carried out through lectures, discussions and practices guided by the service team. The participants of this training were 9 (nine) managers from the technical and management implementation levels. After the training, KGI managers are expected to produce a business design with an integrated business model This service is considered important strategic efforts in developing KGI's role in increasing business potential as a learning center, especially answering Indicators. Keywords : Business Plan, KGI, IKU